Estudo da variabilidade espacial e vertical da temperatura do ar e um estudo de caso da umidade relativa do ar na Floresta Nacional de Caxiunã - Pará - CASTRO, Sirlene de Lima (2019)
The Amazonian forest has been focus of many studies due the great biodiversity and for the regional and global climate contribution, in such a way it is important to know the behavior of the meteorological variables in the forest. This work has as objective to study the behavior of the temperature and the relative moisture in the National Forest of Caxiuanã, observing the relation to topographical variation and canopy height, through the continuous data collection during a period in the rain and dry season. The found results, show that the temperature possesses have daily thermal amplitude and seasonal decrease, being that in the rainy period the daily amplitude is minor in comparison to the dry period. The conclusion is that the temperature does not possess a trend of variation with regard to the differences in topography, in both the stations of the year, and that with regard to the canopy height, the temperature diminishes to the measure that rises in the atmosphere. However when it studied a precipitation event in one very dry month, a phenomenon called thermal inversion was observed that the temperature in the periods of the mornings to hold off form opposes in the period of the afternoon, characterizing. The relative moisture seems to follow the temperature phenomenon.